Effects of homogenous–heterogenous reactions and hybrid nanofluid on Bödewadt flow over a permeable stretching/shrinking rotating disk with radiation - Abu Bakar, Shahirah; Wahid, Nur Syahirah; Md Arifin, Norihan; Pop, Ioan (Springer Nature, 2024)
A nanofluid refers to the dispersion of nanoparticles in a regular fluid and has a unique application in various sectors, including medicine, engineering, and technology. When multiple nanoparticles are suspended in a regular fluid, it creates a hybrid nanofluid. In this study, we aim to investigate homogenous–heterogenous reactions in Bödewadt hybrid nanofluid flow over a permeable rotating disk with radiation. The base fluid chosen for this study is water (H2O), while the nanoparticles iron oxide (Fe3O4) and cobalt ferrite (CoFe2O4) are utilized to create the hybrid nanofluid. An appropriate method of similarity transformation is executed along a set of partial differential equations (PDEs) that were reduced to a system of nonlinear ordinary differential equations (ODEs). Numerical outcomes were then obtained via bvp4c in MATLAB software, with the influence of various parameters such as nanoparticle volume fraction, homogenous/heterogenous reaction strength parameters, suction, shrinking/stretching parameters, and radiation parameter. Additionally, asymptotic analysis was conducted to show that the concentration boundary layer on the disk can be performed subject to a large number of suctions. The present findings reveal that a rise in the volume fraction of nanoparticles results in a reduction in radial velocity profiles, temperature profiles, and tangential fields. As thermal radiation levels rise, a notable reduction in the local Nusselt number is evident. Moreover, there is an observed linear escalation in wall surface concentration when the heterogeneous strength parameter attains higher values. The presented results demonstrate that all flow fields are significantly affected by the participating parameters. © King Fahd University of Petroleum & Minerals 2024.